The Sources of English Phraseological Units with Onomastic Component (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The present article discloses etymology of some English phraseological units with onomastic component, i.e. proper name. There are examples of phraseological units which were formed from different sources including Bible, literature, history, culture, etc.